ETHNOPHARMACOLOGY STUDY OF MEDICINAL PLANTS UTILIZED FOR HYPERCHOLESTEROLEMIA TREATMENT ON BORNEO ISLAND OF INDONESIA - Nuning Rahmawati; Fanie Indrian Mustofa; Sari Haryanti; Dyah Subositi; Harto Widodo; Ika Yanti Marfuatush Sholikhah; Yuli Widiyastuti (Jurnal Tumbuhan Obat Indonesia, 2022)
The use of medicinal plants for various health purposes has been widely reported. This study aimed to inventory knowledge related to the use of medicinal plants, in particular, to treat hypercholesterolemia in the community by traditional healers on Borneo Island, Indonesia. The data collection was based on purposive random sampling using a semi-structured questionnaire among selected traditional healers. The study results exhibited that Syzygium polyanthum was recognized as the most cited plant (UV=0.22) by traditional healers in the treatment of hypercholesterolemia, mostly for internal administration route (93.33%) either in a single compound (66.67%) or in combination (33.33%) with other medicinal plants. Leaves were determined as the most explored and utilized plant part (66.67%) compared to other parts. Most of the medicinal plants were collected from the home yard (60.00%), however, only 37.5 percent were cultivated. In conclusion, this study revealed the important roles of medicinal plants as well as traditional healers in maintaining community health, especially for the treatment of hypercholesterolemia on Borneo Island.